2022
DOI: 10.1186/s13102-022-00405-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical and technical demands of Australian football: an analysis of maximum ball in play periods

Abstract: Background This study compares ball in play (BiP) analyses and both whole game (WG) and quarter averaged data for physical and technical demands of sub-elite Australian football (AF) players competing in the West Australian Football League across playing positions. Methods Microsensor data were collected from 33 male AF players in one club over 19 games of the 2019 season. BiP time periods and technical performance data (e.g., kicks) were acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Previous research has consistently recommended that training intensities should match, or overload, those recorded during maximum periods of play from competitive matches (5,18,25,26,28). In addition, training drills should be devised and incorporated within training regimens that replicate maximum periods of play (12,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has consistently recommended that training intensities should match, or overload, those recorded during maximum periods of play from competitive matches (5,18,25,26,28). In addition, training drills should be devised and incorporated within training regimens that replicate maximum periods of play (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown their data to demonstrate acceptable levels of reliability and validity (20). These events were used to describe BiP periods, which started with an umpire center bounce or throw-in, or where a player returned the ball with a kick in, until a time where the umpire considers the ball to be out of bounds or signals that a goal or behind has been scored, in line with previous research (28). Previous research has reported the identification of these events to show acceptable levels of accuracy among trained coders (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the players were grouped into three positional groups (backs, midfield and forwards). Despite the use of general positional groups being standard practice within AF research [16,39,40], the running demands of AF players can be delineated further into smaller groups (e.g., half backs and full backs), which may provide a greater level of detail [1]. This would require a substantially larger sample size, which if achieved, may also enable the inclusion of the ruck position.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%